2013
DOI: 10.1590/s0103-65642013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Religiosidade e espiritualidade em oncologia: concepções de profissionais da saúde

Abstract: Resumo: A literatura especializada vem identificando influências positivas e negativas de crenças religiosas e espirituais no enfrentamento de enfermidades, tais como o câncer. Sendo assim, a presente investigação teve como objetivo conhecer, analisar e compreender as concepções de profissionais da saúde acerca da associação entre religiosidade, espiritualidade e saúde em Oncologia. Em uma primeira etapa, utilizou-se um questionário eletrônico, respondido por 85 profissionais. Na etapa posterior, sete profissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
28

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 39 publications
0
11
0
28
Order By: Relevance
“…The majority of these studies (29) were performed in healthcare contexts, especially with patients under treatment for chronic diseases such as: kidney failure (Valcanti et al 2012;Pilger 2015;Santos et al 2017), hepatitis C (Reis 2012), multiple sclerosis (Amoroso 2009), liver diseases (Martins et al 2012), epilepsy (Tedrus et al 2013); drug abuse (Correa 2016), cancer (Matos et al 2017;Gobatto 2012;Mesquita et al 2013;Borges 2015;Veit and de Castro 2013;Marucci 2012;Tarabay 2014) HIV AIDS (Faria and Seidl 2006;Pilger 2015;Pinhol et al 2017), and also among informal caregivers of elderly inpatients (Vitorino et al 2017). All of them highlight the more frequent use of positive than negative religious coping.…”
Section: Literature Review: Emprirical Studies On Spiritual/religiousmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of these studies (29) were performed in healthcare contexts, especially with patients under treatment for chronic diseases such as: kidney failure (Valcanti et al 2012;Pilger 2015;Santos et al 2017), hepatitis C (Reis 2012), multiple sclerosis (Amoroso 2009), liver diseases (Martins et al 2012), epilepsy (Tedrus et al 2013); drug abuse (Correa 2016), cancer (Matos et al 2017;Gobatto 2012;Mesquita et al 2013;Borges 2015;Veit and de Castro 2013;Marucci 2012;Tarabay 2014) HIV AIDS (Faria and Seidl 2006;Pilger 2015;Pinhol et al 2017), and also among informal caregivers of elderly inpatients (Vitorino et al 2017). All of them highlight the more frequent use of positive than negative religious coping.…”
Section: Literature Review: Emprirical Studies On Spiritual/religiousmentioning
confidence: 99%
“…The other studies included 2 master's theses (Gobatto 2012;Gryschek 2013) and 1 doctoral dissertation (Brito 2016). Gobatto (2012) developed a study with 85 healthcare professionals (social workers, biologists, doctors, nutritionists, dentists, nurses, psychologists, nurse technicians) to evaluate the comprehension of healthcare professionals (oncology area) regarding the association of health, religiosity and spirituality.…”
Section: Literature Review: Emprirical Studies On Spiritual/religiousmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible benefits of religious beliefs, in some situations experienced in the expectation of death, are: relief of fear and uncertainties, coping and emotional comfort. 8 Spirituality/religiosity, as a form of help in coping with oncological diseases, was considered important for patients in the Mesquita study, 9 but the results showed that the subject is not addressed by the majority of professionals in the context of health and that the subjects of this research revealed that they would like to receive some spiritual care during their treatment. Regarding this aspect, it is emphasized that the influence of religiosity and spirituality on the quality of life of patients with cancer is extremely significant and that once the diagnosis is confirmed, this religiousness of the individual intensifies, with a view to improving the quality of life.…”
Section: Introductionmentioning
confidence: 81%
“…Esses cuidados devem ser oferecidos quando há necessidade de apoio familiar e emocional, falta de perspectiva para o futuro, solidão e depressão (26). Nesse contexto, as necessidades espirituais da família também foram mencionadas e a religião e a espiritualidade foram fontes de conforto importantes para lidar com a experiência de adoecimento de um membro familiar (28 Os enfermeiros também mencionaram outras maneiras de prestar o cuidado espiritual, a partir de conversa e escuta, do toque, como pegar na mão do paciente ou dar-lhe um abraço, das trocas de sentimentos e de energia, de oferecimento de música e de acolhimento. Estas são outras formas de prestar o cuidado espiritual, que, segundo estudos, oportunizam a criação de vín-culo, que é fundamental dada a centralidade da conversa para o estabelecimento do cuidado espiritual (24,26).…”
Section: Maneiras De Prestar O Cuidado Espiritualunclassified